Differential Pulse Anodic Stripping Voltammetric Determination of Selenium(IV) With a Vitamin E-Nafion Modified Gold Electrode - Aziz Ramadan, Abdul; Mandil, Hasna; Ozoun, Amer (Asian Journal of Chemistry, 2010)
Differential pulse anodic stripping voltammetric determination of selenium(IV) using a vitamin E-nafion modified gold electrode has been studied. Selenium(IV) was determined in an aqueous HClO4 medium of pH 1.10 at an accumulation potential of -240 mV and an accumulation time of 300 s. Under the optimum conditions, liner calibration graph, Ip = f(CSe4+ ), was obtained in the concentration ranges of 5 × 10-8-1 × 10-5 mol L-1 with relative standard deviations (RSD) 4.5 %. This method shows that the results for the determination of Se4+ using vitamin E-nafion modified gold electrode were more sensitive and accurate than that obtained using bare gold electrode. The sensitivity was increased about 200 times.